Risk-based stratified primary care for common musculoskeletal pain presentations: qualitative findings from the STarT MSK cluster randomised controlled trial - Benjamin Saunders; Adrian Chudyk; Joanne Protheroe; Vincent Cooper; Bernadette Bartlam; Hollie Birkinshaw; Nadine E Foster; Jonathan C Hill (BMC Primary Care, 2022)
Abstract Background The STarT MSK cluster randomised controlled trial (RCT) investigated the clinical- and cost-effectiveness of risk-based stratified primary care versus usual care for patients with back, neck, shoulder, knee or multi-site pain. Trial quantitative results showed risk-based stratified care was not superior to usual care for patients’ clinical outcomes, but the intervention led to some changes in GP clinical decision-making. This paper reports a linked qualitative study exploring how risk-based stratified care was perceived and used in the trial, from the perspectives of clinicians and patients. Methods Semi-structured interviews were conducted with 27 patients, and focus groups and interviews with 20 clinicians (GPs and physiotherapists) in the intervention arm of the trial. Data were analysed thematically and findings explored using Normalisation Process Theory (NPT) and the COM-B model. Main findings Risk-based stratified care (subgrouping and matching treatments) was found to have ‘coherence’ (i.e. made sense) to several clinicians and patients, in that it was well-integrated in practice, and supported clinical decision-making. However, for some GPs stratified care was less ‘meaningful’, as the risk-stratification tool did not fit with usual ways of consulting and added to already time-pressured consultations. GPs reported giving more patients written information/advice due to easier access to electronic information leaflets through the trial template and were motivated to refer patients to physiotherapy as they believed the trial resulted in faster physiotherapy access (although this was not the case). Patients and clinicians reported that risk-based stratified care influenced conversations in the consultation, prompting greater attention to psychosocial factors, and facilitating negotiation of treatment options. Physiotherapists saw benefits in receiving information about patients’ risk subgroup on referral forms. Conclusion These findings provide context for interpreting some of the trial outcomes, particularly in relation to changes in clinical decision-making when risk-based stratified care was used. Findings also indicate potential reasons for lack of GP engagement with risk-based stratified care. Positive outcomes were identified that were not captured in the quantitative data, specifically that risk-based stratified care positively influenced some GP-patient conversations and facilitated negotiation of treatment options. Trial registration ISRCTN15366334 (26/04/2016).